Global land reform experiences: A review for South Africa - Davies, Rob; Kosec, Katrina; Nkonya, Ephraim M.; Song, Jie (United Nations University, 2020)
This paper reviews land reform in six emerging market economies with some similarities to South Africa, and in sub-Saharan African countries, which share a similar colonial history. While care needs to be taken when trying to transplant policies that have worked in other countries, the paper suggests a number of broad lessons. Land reform is a process, not an event: reform programmes need not be set out in full and written in stone at the outset. Particular reforms can be phased in over time in different parts of a country, rather than awaiting a grand design. It is neither necessary nor desirable to make a binary decision between state-led and market-assisted reforms; different approaches can advantageously be taken simultaneously. Markets are particularly important for post-reform success. Flexibility and pragmatism can lead to greater learning, improving effectiveness of reforms over time. Democratic politics are important, both in creating the demand for redistribution and in contributing to its success. Land reforms are generally unsuccessful unless accompanied by complementary support. Reforms can lead to broader growth, in part by creating the basis for an inclusive economy.